Statistical significance and other complementary measures for the interpretation of the research results - Torres, Mildrey; Herrera, Magaly; García, Yaneilys (Cuban Journal of Agricultural Science, 2023)
The contrast hypothesis constitutes the most used method in the scientific research to estimate the statistical significance of any find. However, nowadays its use is questionable because it did not have other statistical criteria that make possible the credibility and reproducibility of the studies. From this condition, this study review how the use of the null hypothesis significance testing has been and the recommendations made regarding the application of other complementary statistical criteria for the interpretation of the results. It is described the main controversy of only use the probability value to reject or accept a hypothesis. The interpretation of a non significant value, as prove of effect absence or a significant value as existence of it, is a frequent mistake in scientific researchers, according to the reviewed literature. It is suggested to make a rigorous assessment of the obtained data in a research and include in the study reports other statistical tests, as the test power and the effect size of the intercession, to offer a complete interpretation and increase the results quality. Specifically, it is recommended to the editors of scientific journals to consider the report of the mentioned statisticians in the papers who required, as part of the criteria to take into account for their evaluation. Key words: null hypothesis significance testing, probability value, statistical power, effect size